Is utilisation of computed tomography justified in clinical practice? Part IV: Applications of paediatric computed tomography - Sun, Z.; Ng, K.H.; Sarji, S.A. (Singapore Medical Assoc, 2010)
Computed tomography (CT) has been recognised as the most widely used imaging technique in both adults and children, owing to technological developments, especially with the recent innovations in multislice CT. This has resulted in an increase in the use of CT examinations in children younger than 15 years of age in developed countries. The increasing use of paediatric CT in clinical practice has raised concerns regarding the potential risk of radiation-induced malignancy. This is because CT examinations deliver a much higher radiation dose than conventional radiographic techniques. Children are more sensitive to radiation exposure than adults and have a longer time ahead of them to manifest radiation-induced effects and injuries. Therefore, it is of paramount importance to reduce or minimise the radiation dose to children when choosing CT as the major imaging modality for diagnostic purposes. This article reviews the clinical applications of paediatric CT with regard to the adjustment of imaging protocols in routine clinical practice and in the emergency department, the justification of CT use in paediatric imaging, clinical awareness of CT-associated radiation risk and strategies to minimise radiation exposure to children.